Role Performance of Community Health Volunteers and Its Associated Factors in Kuching District, Sarawak - Hsien, Melvin Liang Chung; Helmy, Hazmi; Whye, Lian Cheah (Hindawi Publishing Corporation, 2017)
The objective of this study was to assess the role performance among KOSPEN community health volunteer in Kuching district and its associated factors.This was a cross-sectional study, conducted in 21 localities in Kuching with a total of 210 respondents. Data were collected using validated interviewer-administered questionnaires and analyzed using SPSS version 22.0. The respondents comprised 55.2% females, 81.9% married, and 41.4% aged above 45 and above and 72.4% completed their education up to secondary school.The result revealed that 59.0% of the respondents agreed and understood their role performances.Multiple Logistics analysis revealed that factors associated with role performance were age group (